Size does matter: determination of the critical molecular size for the uptake of chemicals across the chorion of zebrafish (Danio rerio) embryos - Pelka, Katharina Elisabeth; Henn, Kirsten; Keck, Andreas; Braunbeck, Thomas (Aquatic toxicology, 2017)
In order to identify the upper limits of the molecular size of chemicals to cross the chorion of zebrafish, Danio rerio, differently sized, non-toxic and chemically inert polyethylene glycols (PEGs; 2000-12,000 Da) were applied at concentrations (9.76 mM) high enough to provoke osmotic pressure. Whereas small PEGs were expected to be able to cross the chorion, restricted uptake of large PEGs was hypothesized to result in shrinkage of the chorion. Due to a slow, but gradual uptake of PEGs over time, molecular size-dependent equilibration in conjunction with a regain of the spherical chorion shape was observed. Thus, the size of molecules able to cross the chorion could be narrowed down precisely to ≤4000 Da, and the time-dependency of the movement across the chorion could be described. To account for associated alterations in embryonic development, fish embryo toxicity tests (FETs) according to OECD test guideline 236 (OECD, 2013) were performed with special emphasis to changes in chorion shape. FETs revealed clear-cut size-effects: the higher the actual molecular weight (= size) of the PEG, the more effects (both acutely toxic and sublethal) were found. No effects were seen with PEGs of 2000 and 3000 Da. In contrast, PEG 8000 and PEG 12,000 were found to be most toxic with LC50 values of 16.05 and 16.40 g/L, respectively. Likewise, the extent of chorion shrinkage due to increased osmotic pressure strictly depended on PEG molecular weight and duration of exposure. A reflux of water and PEG molecules into the chorion and a resulting re-shaping of the chorion could only be observed for eggs exposed to PEGs ≤4000 Da. Results clearly indicate a barrier function of the zebrafish chorion for molecules larger than 3000 to 4,000 Da.
Available online 21 December 2016
Gesehen am 06.07.2017